The natural history and epidemiology of insect venom allergy: clinical implications - Bilò, M. B.; Bonifazi, F. (Clinical and experimental allergy, 2009)
Summary Hymenoptera stings can cause severe systemic allergic reactions and occasionally fatal anaphylaxis, which contribute significantly to morbidity and deterioration in health‐related quality of life. The latest epidemiological data confirm the importance of insect sting allergy as a cause of anaphylaxis. Despite the high prevalence of asymptomatic sensitization, the prevalence of sting‐induced systemic reactions (SRs) is low. However, to date, no parameter has been identified that can predict who will have a future reaction and whether it will be a large local reaction or anaphylactic. The combination of several concomitant factors, which include environmental, genetics and individual factors, may account for the occurrence of a system reaction in individual patients. Several not completely known factors may be associated with the severity of systemic re‐stings. As about 50% of subjects with fatal sting reactions had no documented history of a previous SR, greater insight of the natural history and risk factors is required, especially in asymptomatic sensitized subjects. For patients with SRs, prevention of future severe allergic reactions starts with referral to an emergency department, correct administration of epinephrine by medical staff, referral to an allergist and coaching for the self‐administration of epinephrine. However, most insect sting victims failed to seek medical advice and hospital attendance does not always correlate with the severity of the allergic reaction. Moreover, only about one‐third of patients received a prescription for self‐injectable epinephrine and were officially referred to an allergist after being discharged, causing the non‐ or delayed prescription of specific immunotherapy. Significantly, this means that at least half of the sting fatalities in patients with a positive history could have been avoided through the timely administration of specific immunotherapy. These findings indicate the urgent need to educate the general population and doctors on the management of venom‐allergic patients.